2018
DOI: 10.1093/tas/txy132
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography as a tool to detect hoof lesions in sheep

Abstract: Lameness has a major negative impact on sheep production. The objective of this study was to 1) quantify the repeatability of sheep hoof temperatures estimated using infrared thermography (IRT); 2) determine the relationship between ambient temperature, sheep hoof temperature, and sheep hoof health status; and 3) validate the use of IRT to detect infection in sheep hooves. Three experiments (a repeatability, exploratory, and validation experiment) were conducted over 10 distinct nonconsecutive days. In the rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…Minimum, average, and maximum IRT of user-defined external body surfaces are determined for each thermogram using the relevant software. Changes in the maximum IRT of external body surfaces are better associated with changes in the behavioural responses of emotions, lactation variables, and metabolism than average or minimum IRT values [ 31 , 32 , 112 , 113 , 114 , 115 ]. Minimum and average IRT calculation are prone to variation in positioning of the frame of the thermogram, as well as external factors such as adhesion of water droplets and mud or faeces on external surfaces.…”
Section: Cattle Responses To Heat Stress and Their Measurementmentioning
confidence: 99%
“…Minimum, average, and maximum IRT of user-defined external body surfaces are determined for each thermogram using the relevant software. Changes in the maximum IRT of external body surfaces are better associated with changes in the behavioural responses of emotions, lactation variables, and metabolism than average or minimum IRT values [ 31 , 32 , 112 , 113 , 114 , 115 ]. Minimum and average IRT calculation are prone to variation in positioning of the frame of the thermogram, as well as external factors such as adhesion of water droplets and mud or faeces on external surfaces.…”
Section: Cattle Responses To Heat Stress and Their Measurementmentioning
confidence: 99%
“…Especially for foot inflammation, IRT is used to compare the temperature of the coronary band and foot skin within and between cows, providing a reliable diagnostic tool [94,95,96]. The diagnostic significance of IRT has been recently demonstrated in sheep [93,97]. The aforementioned research group [93] compared the application of IRT with standard measurements of temperature and oxidative stress biomarkers in sheep, and concluded that both of them could be applied in the early diagnosis of foot lesions and lameness in sheep.…”
Section: Diagnosis Of Foot-related Lamenessmentioning
confidence: 99%
“…The aforementioned research group [93] compared the application of IRT with standard measurements of temperature and oxidative stress biomarkers in sheep, and concluded that both of them could be applied in the early diagnosis of foot lesions and lameness in sheep. However, targeted adjustments, based on the ambient temperature and productivity stage, need to be implemented to improve the diagnostic capability of IRT in discriminating the occurrence and severity of foot-related lameness in sheep [97].…”
Section: Diagnosis Of Foot-related Lamenessmentioning
confidence: 99%
“…The images can be used to identify differences in external/skin temperature that can be related to inflammatory process, infection, necrosis, stress, and overall health. In research, infrared thermography (IRT) has been used to identify mastitis in dairy cattle and sheep (63,64), and for digital dermatitis in sheep (68), showing the capability to classify healthy and clinically sick animals. Moreover, in a controlled study Metzner et al (65) observed that IRT was capable of detecting an increase in udder temperature ∼10 h after inoculation with E. coli.…”
Section: Identification Of Mastitis and Digital Dermatitis By Thermogmentioning
confidence: 99%